2021
DOI: 10.1007/s40279-021-01459-0
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of ‘Durability’ in the Physiological Profiling of Endurance Athletes

Abstract: Profiling physiological attributes is an important role for applied exercise physiologists working with endurance athletes. These attributes are typically assessed in well-rested athletes. However, as has been demonstrated in the literature and supported by field data presented here, the attributes measured during routine physiological-profiling assessments are not static, but change over time during prolonged exercise. If not accounted for, shifts in these physiological attributes during prolonged exercise ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 91 publications
(124 reference statements)
2
55
0
Order By: Relevance
“…However, repeated maximal performance (of similar durations) is a determinant of success in several individual and team sports formats, which may require athletes to contest a heat and a final, or multiple rounds of competition in one day e.g., athletics, cycling or rugby sevens. Therefore, a proposed extension to the line of inquiry established by the present work is that of either or both athlete durability (as per Maunder et al [ 70 ]) and repeatability, where athletes’ decay in performance is assessed during prolonged exercise or with and without sufficient recovery between trials, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, repeated maximal performance (of similar durations) is a determinant of success in several individual and team sports formats, which may require athletes to contest a heat and a final, or multiple rounds of competition in one day e.g., athletics, cycling or rugby sevens. Therefore, a proposed extension to the line of inquiry established by the present work is that of either or both athlete durability (as per Maunder et al [ 70 ]) and repeatability, where athletes’ decay in performance is assessed during prolonged exercise or with and without sufficient recovery between trials, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Intertest reliability is an important determinant of assessing change within an athlete as a result of a nutritional or training intervention, with pacing and performance levels being pertinent factors that are documented to influence three-minute all-out test performance [ 40 , 69 , 70 ]. Average power and end power obtained during a three-minute all-out test have been shown to be reliable between repeated trials [ 48 , 49 ], hence our focus on these metrics as performance thresholds for indicating meaningful change between interventions, as per Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Athlete #1 had a baseline peak oxygen uptake during incremental running on a treadmill until exhaustion of 80 ml/min/kg, which can be considered rather good and comparable to that reported for endurance athletes, but not exceptional. A major determinant of endurance performance is not only peak oxygen uptake, but also the fraction that can be maintained for a prolonged time (Maunder et al, 2021 ). Athlete #1 was able to maintain 85% of his altitude adjusted HRmax, and presumably also a large fraction of his altitude adjusted aerobic power, throughout the race, even though some heart rate drift probably occurred (Mattson et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that elements besides rider-density are at work; likely a fatigue component, as similar tendencies have been reported in earlier studies ( Granier et al, 2018 ; Hays et al, 2018 ; Viana et al, 2018 ). Exercise assessment models, such as CP, have been proposed to drift during prolonged exercise and thereby lead to inaccuracies when applied to prolonged durations ( Maunder et al, 2021 ). While little to no change in calculated CP after 80-min heavy intensity exercise has been reported ( Clark et al, 2019a ), continuous exercise approaching 2 h has been shown to be detrimental to both CP and W ', implying a fatigue component unaccounted for by the current CP calculations ( Clark et al, 2018 , 2019a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the aggressive initial laps coupled with frequent high-intensity segments presented by the track led to the positive pacing observed in this study, hindering sufficient recovery between high-intensity bouts. However, the precise fatigue, recovery and durability mechanics that drive the decline are still not adequately described ( Clark et al, 2019a , b ; Maunder et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%